Pengaruh Pemberian Insentif Terhadap Efektivitas Kerja Karyawan Pada Server Pulsa Easytronik SRB Ponsel Tanjung Morawa - Gihon River Peace; Jason Visel; Harpingka Fitria Br. Sibarani (Institute of Computer Science (IOCS), 2018)
This research aims to determine the presence or absence of incentive influence on the effectiveness of work and to measure how much incentive to give the effectiveness of employee work in Server Pulsa Easytronik SRB Ponsel. The research methods used in this research are quantitative research methods, i.e. the research methods based on the philosophy of positivism, used to examine on certain populations or samples, data collection using research instruments, quantitative data analysis/statistics, with the aim to test a predetermined hypothesis. The population in this research is all the employees of Server Pulsa Easytronik SRB Ponsel Tanjung Morawa amounting to 34 people, while the respondents are the entire population. The technique of data collection used is a questionnaire technique, which is a form of data gathering instruments in a written question format that comes with a column where the respondent wrote the answer to the question directed to them. The results of this study showed that the free variable i.e. incentive (x) has positive and significant effect on the bound variable i.e. the effectiveness of the work (y). Where the results are T calculate > T table is 3.481 > 2.037, so it can be concluded that the incentive variables have contributed to the effectiveness of the work. Coefficient of analysis result is 54.5%. This means that incentives have an influence on the effectiveness of the work by 54.5% and the remaining 45.5% are influenced by other variables.